2023
DOI: 10.1111/gwao.12971
|View full text |Cite
|
Sign up to set email alerts
|

“In this together”? Gender inequality associated with home‐working couples during the first COVID lockdown

Abstract: The first lockdown, conferred upon us by the COVID‐19 outbreak in March 2020, created a unique, 3‐month‐long, laboratory‐like situation that made gender relations and women's work especially relevant for social research. Full‐time employed parents who switched to working from home were in a unique position to renegotiate the division of housework, childcare, or the management of school‐related tasks. This paper explores what happened to the gendered division of unpaid work and what factors explain the (failed)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The research on the consequences of COVID-19 initially proposed and found evidence for two opposing hypotheses: 1) the re-traditionalization hypothesis (Allmendinger 2020) that the pandemic will bring back the traditional unequal division of household chores (Çoban 2022;Nagy et al 2023;Wojnicka and Kubisa 2023), and 2) the equalizing hypothesis (Craig and Churchill 2021;Steinmetz et al 2022) that changes in the working hours, income, time and location of work will provide space for both partners to engage more equally in the domestic work. Until now, the studies showed evidence for both, depending on the country and circumstances, the male partner contribution either relatively increased or decreased (Hipp and Bünning 2021;Zamberlan, Gioachin, and Gritti 2022).…”
Section: The Covid-19 Contextmentioning
confidence: 99%
“…The research on the consequences of COVID-19 initially proposed and found evidence for two opposing hypotheses: 1) the re-traditionalization hypothesis (Allmendinger 2020) that the pandemic will bring back the traditional unequal division of household chores (Çoban 2022;Nagy et al 2023;Wojnicka and Kubisa 2023), and 2) the equalizing hypothesis (Craig and Churchill 2021;Steinmetz et al 2022) that changes in the working hours, income, time and location of work will provide space for both partners to engage more equally in the domestic work. Until now, the studies showed evidence for both, depending on the country and circumstances, the male partner contribution either relatively increased or decreased (Hipp and Bünning 2021;Zamberlan, Gioachin, and Gritti 2022).…”
Section: The Covid-19 Contextmentioning
confidence: 99%
“…Despite the increased time spent together, families faced a unique set of challenges during this period. Daily routines were interrupted, and the boundaries between public and private spheres blurred through the adoption of work-from-home practices, causing numerous families to grapple with the challenge of adapting to the profound alterations within their family system (Nagy et al, 2023).…”
mentioning
confidence: 99%
“…This autoethnographic vignette vividly illustrates the extent of stress induced by the lockdown, laying bare the disruptions it caused in the delicate balance between work and family life. It describes the type of tasks that emerged at the onset of the pandemic and the first lockdowns, including the spatial and temporal reorganization of productive and reproductive labor.The transfer of childcare responsibility from collective structures or private individuals to parents during lockdowns has burdened working parents with a simultaneous "double shift": caring for children while fulfilling work obligations without any opportunity for respite between these demanding tasks(André & van der Zwan, 2022;Bühler et al, 2021;Craig & Churchill, 2021;Czymara et al, 2021;Nagy et al, 2023;Refle et al, 2020;Steinmetz et al, 2022).…”
mentioning
confidence: 99%